The host range and distribution pattern of rhizocephalan parasitic barnacles in Korean coasts and their relationship with geographical factors - Jung, Jibom (Frontiers in Marine Science, 2024)
Introduction This study undertakes a detailed examination of the host range and distribution patterns of Rhizocephala, a group of specialized parasitic barnacles, within Korean marine environments. It aims to expand the understanding of their biodiversity and ecological impact. Methods Employing both morphological observation and mitochondrial DNA sequencing, the study identifies the variety of rhizocephalan species infecting decapod hosts in Korean waters, aiming to document their diversity and distribution. Results The investigation identifies 26 rhizocephalan species parasitizing 28 decapod hosts, including the discovery of three new parasite-host relationships not previously reported. It was observed that while a few rhizocephalan species infect multiple hosts, most have a narrow host range. Additionally, the study maps out regional differences in Rhizocephala diversity across three Korean marine ecoregions, noting the highest diversity in the warmer East China Sea ecoregion and lower diversity in the colder Yellow Sea and East Sea ecoregions. Discussion The findings underscore the necessity for continued taxonomic research on Rhizocephala and their host species to better understand and manage these parasites, which hold significant ecological and economic importance. The study suggests that geographical variations in host-parasite relationships are influenced by regional climatic conditions, particularly winter water temperatures.